Microbiota and Ocular Diseases - Xue, Wei; Li, Jing Jing; Zou, Yanli; Zou, Bin; Wei, Lai (Frontiers in Cellular and Infection Microbiology, 2021)
Recent advances have identified significant associations between the composition and function of the gut microbiota and various disorders in organ systems other than the digestive tract. Utilizing next-generation sequencing and multiomics approaches, the microbial community that possibly impacts ocular disease has been identified. This review provides an overview of the literature on approaches to microbiota analysis and the roles of commensal microbes in ophthalmic diseases, including autoimmune uveitis, age-related macular degeneration, glaucoma, and other ocular disorders. In addition, this review discusses the hypothesis of the “gut-eye axis” and evaluates the therapeutic potential of targeting commensal microbiota to alleviate ocular inflammation.